THE URGENCY OF FORMULATING LEGAL REMEDIES BY VICTIMS: A COMPARATIVE STUDY OF INDONESIA AND CHINA - Utami Puspaningsih; Yuliati; Faizin Sulistio (CV. RADJA PUBLIKA, 2025)
Criminal legal remedies are regulated in Chapter XII of the Criminal Procedure Code, namely ordinary legal remedies and extraordinary legal remedies. The interests of victims of crime are represented by the Public Prosecutor, but unfortunately if the Public Prosecutor does not file a legal remedy against the verdict, then the victim cannot file a legal remedy and must accept the verdict. The purpose of this paper is to actualize the participation of victims in criminal justice. The method of this study was normative juridical approach with descriptive analytical specification. The stages of the study were literature research and comparison of legal systems with other countries. This research shows that the participation of victims in judicial practices has become a public concern in the international realm so that it is necessary to balance the roles of victims and defendants in the Indonesian legal system, especially in filing criminal law efforts. Therefore, there is a need for material testing to the Constitutional Court related to Article 50 to Article 68 of the Criminal Procedure Code.